PRAKTIK JUAL BELI VOUCHER TELEPON DI ASRAMA AL ASYIQIE NGAMPEL KEDIRI DALAM PERSPEKTIF EKONOMI ISLAM - Rifda Izzatun Nada; Sutantri (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to determine the practice of buying and selling telephone vouchers at Al Asyiqie Dormitory, Ngampel Kediri, and to analyze it from the perspective of Islamic economics. Telephone vouchers are provided as a means of communication for students who do not return home for one full year so that they can stay in touch with their parents and families. This research uses a qualitative approach with field research methods. Data collection techniques were carried out through observation, interviews, and documentation. The results show that the sale and purchase of telephone vouchers are carried out by the dormitory security administrators with voucher denominations of IDR 6,000, IDR 12,000, IDR 18,000, IDR 25,000, IDR 26.000 and IDR 65,000, at a price of IDR 1,000 per minute. The contract is carried out verbally, and transactions take place based on the willingness of both parties. This practice is not considered a monopoly because it aims to meet the students' needs rather than to seek excessive profit. From the perspective of Islamic economics, this practice has fulfilled the pillars and conditions of sale and purchase and does not contain elements of gharar or fraud. However, the aspect of price fairness still needs attention because some students consider the price quite expensive. Therefore, an evaluation of price fairness is needed so that the principle of justice in Islamic economics can be optimally realized.